THE CONSUMER GOODS IN THE ADVERTISEMENTS OF THE BELLE ÉPOQUE PERIOD IN PELOTAS, IN SOUTHERN BRAZIL, RELEASED BY MAGAZINE ILLUSTRAÇÃO PELOTENSE - Marroni, Fabiane Villela; Oliveira, Ana Claudia de (Laboratório Editorial FCL-UNESP, 2016)
The Belle Époque was a period of political, economic and socio-cultural changes. It originated in France in the late 19th century, illuminated by the ideals of the French Revolution and the Industrial Revolution. Changes, progress and freedom form the central theme of a journey in search of civility, in modern speech. A worldview that is enunciated with marks of an “other”, in a euphoric period of changes in the way of life of society. For this reason, what is proposed in this academic work is to analyze the way of life of Pelotas’ society and its visibility through consumer goods reported in the local print media, in a period characterized as the Belle Époque. The object of study chosen was the magazine Illustração Pelotense, which remained in activity between the years 1919 and 1925. This choice is justified by the significant circulation of the editions, which shows the interest of the readers. As theoretical and methodological basis, we used the theory of discursive semiotics, from Barros (1990), Landowski (1992) and Oliveira (1997).